2004
DOI: 10.1016/j.nuclphysb.2004.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Spinor field realizations of non-critical strings

Abstract: In this paper, we construct the nilpotent Becchi-Rouet-StoraTyutin(BRST ) charges of spinor non-critical W 2,s strings. The cases of s = 3, 4 are discussed in detail, and spinor realization for s = 4 is given explicitly. The BRST charges are graded.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Substituting ( 38) into (34), one can obtain the spin-6 current W , which together with the T = T 0 generate the W 2,6 algebra. Substituting T and W into (33), we will obtain the explicit form of the BRST operator Q B for W 2,6 algebra.…”
Section: Brst Operator For W 26 Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting ( 38) into (34), one can obtain the spin-6 current W , which together with the T = T 0 generate the W 2,6 algebra. Substituting T and W into (33), we will obtain the explicit form of the BRST operator Q B for W 2,6 algebra.…”
Section: Brst Operator For W 26 Algebramentioning
confidence: 99%
“…The spectrum of W strings also can be found in [27,28,29,30,31,32]. The spinor realizations of W 2,s strings were given in [33,34,35,36]. It is known that, when extended to the quantum case, W 2,s algebras will become non-linear.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the BRST charges of the W 2,s strings and W N strings are graded, the exact spinor field realizations of W 2,s (s = 3, 4, 5, 6) strings and W N (N = 4, 5, 6) strings were obtained [24,25,26,27]. Recently, we constructed the nilpotent BRST charges of the spinor non-critical W 2,s (s=3,4) strings by taking account of the property of spinor field [28]. It was shown that certain integer W 2,s (s=3,4) algebras can be linearized as the W 1,2,s algebras by the inclusion of a spin-1 current.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion 11were obtained [24,25,26,27]. Recently, we constructed the nilpotent BRST charges of the spinor non-critical W 2,s (s=3,4) strings by taking account of the property of spinor field [28]. It was shown that certain integer W 2,s (s=3,4) algebras can be linearized as the W 1,2,s algebras by the inclusion of a spin-1 current.…”
mentioning
confidence: 99%
“…This provides an easy way to construct W 2,s strings, while it imposes more constrain conditions on the BRST charge. Under the supposition that this grading form still holds true for spinor field realizations, the corresponding works had been done [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%